Economic Development - Shahor, Tal (European Journal of Economics and Business Studies, 2015)
Economic development is a process aimed at improving the quality of life of the citizens which can be achieved by increasing the national income. This increase includes: increased household income (employee salaries and self-employed profits), and no less important, increased taxes which would facilitate an improvement in the services that citizens receive from government system. To achieve improved quality of life, it is important that the additional income does not simultaneously increase the disparity between rich and poor (which is liable to occur if the main beneficiaries of the increase in income are the financiers and the managerial level). It should also not lead to an increase in unemployment (as sometimes occurs when companies go through a streamlining process), or cause environmental pollution. Additionally, to improve the quality of life, attention must be given to other areas such as education, culture, health, etc. which all require extensive resources, and their development is therefore also a matter of economic interest. The goal of this article is to present the principles and processes required to facilitate economic development without harming other components that comprise the quality of life.